The Political System of Brazil - de la Fontaine, Dana.; Stehnken, Thomas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg (Imprint), 2016)
This volume presents in-depth insights into the polity, politics and policies of the Brazilian political system. It reassesses the processes of change since the country's return to democracy in the 1980s, in the light of autocratic societal structures and suboptimal institutional design, on the one hand, and the political and economic achievements observed, on the other. In their contributions, top Brazilian and international scholars critically examine the development of the political system with a focus on the Lula and Rousseff administrations, and place their actions and failures in the socio-political and economic context so as to uncover the underlying institutional structures, constellations and diverging interests of actors on various decision-making levels and in different political fields. It is the central aim of this book to present a differentiated portrait of the current political landscape and remaining contradictions in Latin America's largest country.
Introduction -- Part I: Historical Legacies and Socio-Economic Inequalities -- Part II: Checks and Balances in the Political System since 1988 -- Part III: Institutions of Interest Representation -- Part IV: Policy Fields.
Keywords: Political science; Social policy; Culture-Study and teaching; Economic policy